The mechanisms of ischemic mitral insufficiency - S. A. Rudenko; O. M. Trembovetstka; O. K. Gogayeva; V. G. Tanskyi; A. V. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2016)
In National Institute of Cardiovascular surgery NM Amosov in the period from 1 January 2012 to 31 December 2014 was performed 142 interventions on the mitral valve in patients with coronary heart disease and ischemic mitral regurgitation.The average patient age was 61.8±7.4 years. The majority of patients with coronary artery disease and comorbid medical devices marked complicated background. Hypertensive heart disease was diagnosed in 59,9% (n=85) of patients, with diabetes mellitus – 14,8% (n=21), peripheral arterial disease – in 16,2% (n=23), acute cerebrovascular accident in history – in 3,5% (n=5).Plastic surgery were performed in 93 (65.5%) patients, mitral valve replacement – in 49 (34.5%).The development of mitral insufficiency is dependent upon the nature of left ventricular remodeling. Selection of surgical treatment depends on the anatomic changes of the valve unit and the geometry of the left ventricle.